Critical Discourse Analysis Of Campus News Text : Model of Theo Van Leeuwen (Case Study of UIN Malang News on Online Media jatim.nu.or.id) - Moch Nurcholis Majid; Muchammad Wildanil Mubarok (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2023)
This research aimed to (1) describe and analyze the exclusion and inclusion strategy of the UIN Malang campus news text on the website jatim.nu.or.id (2) described and analyzed the comparison of the exclusion and inclusion strategy of the UIN Malang campus news text on the jatim.nu website. or.id. This type of descriptive qualitative research used observation, documentation, and writing data collection techniques. Theo Van Leeuwen's discourse model The data in this research were news sentences containing Theo Van Leeuwen's discourse theory. The results showed that the inclusion strategy was more widely used in UIN Malang campus news on the website jatim.nu.or.id, tending to use an inclusion strategy (indifferentiation-differentiation) in producing the news (22%) with the aim of providing additional information to clarify the boundary between two parties reported. Based on these conclusions, there were several suggestions that couldbe conveyed, namely: (1) readers to be more critical and careful in sorting out information, (2) media owners were expected to be able to produce news in a more balanced manner, (3) other researchers could conduct similar research on other media and also on the focus of other news.